Analisis Pelaksanaan ANBK Terhadap Literasi dan Numerasi Kesiapan Siswa dan Pemanfaatan TIK di SMP Satu Atap 1 Maliku Kalimantan Tengah - Gafelina; Hastuti, Dwi; Fauziah, Syifa; Nisa, Vika Zakiyatun; Nurakbar, Tomy; Jabar, Abdul; Edde, Genta Primadana (PANDITA: Interdisciplinary Journal of Public Affairs, 2026)
This study aims to examine the implementation of the Computer-Based National Assessment (Asesmen Nasional Berbasis Komputer/ANBK) as an effort to strengthen students’ literacy and numeracy competencies at SMP Negeri Satu Atap 1 Maliku, Central Kalimantan, with particular attention to student readiness and the utilization of Information and Communication Technology (ICT). This research employed a qualitative descriptive approach involving school operators, teachers, and students who participated in the ANBK. Data were collected through classroom observations, in-depth interviews, and analysis of students’ numeracy literacy test results. The findings indicate that the majority of students’ numeracy literacy skills fall within the medium and low categories. Students experience significant difficulties in understanding contextual word problems, selecting appropriate problem-solving strategies, and applying mathematical concepts in real-life situations. These challenges are further compounded by limited ICT infrastructure, insufficient access to digital devices, unstable internet connectivity, and students’ varying levels of technical competence and psychological readiness when facing computer-based assessments. The school has utilized the Education Report Dashboard as a reference for evaluating learning outcomes and planning follow-up actions. However, the integration of ANBK data into systematic school programs remains limited and has not yet optimally informed instructional improvement. Therefore, this study highlights the need for strengthening ICT facilities, enhancing teachers’ and students’ digital literacy, and conducting regular ANBK simulations to improve readiness and maximize the role of ANBK as a tool for improving literacy and numeracy learning quality in schools, particularly in disadvantaged and remote areas.